ANALISIS KINERJA PERUSAHAAN PERBANKAN SEBELUM DAN SESUDAH MENJADI PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA (BEJ) - Astuti Yuli (Jurnal Riset Akuntansi dan Keuangan, 2006)
Go pubtic is selling.stock or o company obligation to the public in the stock market, in which by Initial Public ffiring QPO). Go pubtic compay will receive fund or cash, therefore it is expected that the company prospect ningt get better throught the expasio, which is doheIn this research, it is doe empiris study to is public bank sample. He sample are take by purposive sampling fr.om 2l banlcs listed on BEJ. History list are got. from the bank Jinancial report approximate years of age lasted o 3l December. We hope that the study result can give answer the questioh "Is there dffirence between company workingof banking cornpany before and afier become public compay"?Some studies on the effict of go public on Jakarta Stock Exchaneshowed that there have been significant positive effects o the comprya working system, conversely, the other research gave iconnsistent /inding.Furthermore, this research dimed to analyze the dffirent of thebanking system in the years before and afier the go public. The banking working systen was measured based on five aspects, they are: 1) Capital adeguacy, 2) Asset quality, 3) Management, 4) Earning and 5) Liquidity.The result of hypothesis show a conclusion that oly some of dffirent CAMEL ratio are ROM and NPM for the years before and after go public, and the totatity show that there is no significant dffirence between bank company working for the years before and arter go public. On the onther word, the result of new contribution selling on IPO did ,not fuove positivg ffict to improvement of bank company worki.ng after listing.Kqwords : IPO, banking, go public, CAMEL.